THE EFFECTS OF PRE – SHOT ROUTINE AND POST ACTIVATION POTENTIATION WARM-UP PROGRAMS ON DRIVER CLUBHEAD SPEED IN AMATEUR GOLFERS - Yeemin, Wichai; KEMARAT, Supatcharin; THEANTHONG, Apiluk (Journal of Sports Science and Technology, 2018)
The purposes of this research were to compare the effects of a pre-shot routine plus warm-up program, pre-shot routine program, and warm-up program on driver clubhead speed in amateur golfers prior training and after six weeks training, and to compare the driver clubhead speed among groups. Participants of this study were 15 Thai amateur golfers. Mean age 19.87± 0.92 years with handicap score mean 4.87±2.36 points. Researchers separated the participants into three groups with five people each of group and set each group with one training program. Group 1 pre-shot routine plus warm-up program, group 2 pre-shot routine program, and group 3 warm-up program. Data collection used Golf Simulator. Mean, standard deviation, frequency, percentage, one-way analysis of variance, and dependent sample test was used to analyze data. This study set the P-value at .05 for the significance test. Research findings showed that driver clubhead speed among groups was not statistically significant (p > 0.05). The study also showed no statistical significance when compared between prior and after six weeks of training in each group. However, the pre-shot routine program and warm-up program groups, it was found that had more driver clubhead speed after six weeks of training. The results of this study indicated the effectiveness of the driving that can be improved through training a pre-shot routine program and active dynamic warm-up plus post-activation potentiation technique program. (Journal of Sports Science and Technology 2018; 18(2): 99-108) Keywords: Pre–shot routine, Post activation potentiation, Active dynamic-warm up, Amateur golfers *Corresponding Author: Wichai YEEMIN Faculty of Allied Health Sciences, Thammasat University, Klong Nueng, Klong Luang, Pathumthani, Thailand 12120.